TEOLOGI SEKS DALAM PENCIPTAAN KETURUNAN SUPUTRA - I Wayan Titra Gunawijaya (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2019)
Fulfilling the purpose of human life in accordance with the teachings of Hinduism are Dharma, Artha, Kama, and Moksha. These four goals become the rules by Hindus in living their lives. Through Dharma man can get knowledge that begins, through artha man can enjoy material life, through kama man can enjoy life in satisfaction, through moksha man can free himself from worldly bonds. Specifically studying Kama, humans are required to have lust including seksual lust because it will be related to obtaining offspring. Various Hindu literature explains about seksual knowledge from various ways of enjoying seks. In the Kama Sutra is a special book discusses how, the process of having seksual relations, and restrictions on carrying out these relationships. Furthermore, in Wadhu Tattwa explains about obtaining an ideal beauty both spiritual beauty and physical beauty. Both of these literature are inseparable from the goal is to obtain offspring or future generations.